2023
DOI: 10.1002/edn3.462
|View full text |Cite
|
Sign up to set email alerts
|

Detection of environmental DNA from amphibians in Northern Europe applied in citizen science

Steen Wilhelm Knudsen,
Martin Hesselsøe,
Maria Rytter
et al.

Abstract: Many species of amphibians in Northern Europe are threatened and the local distributions are rarely described in detail. Application of modern molecular methods provides an important supplementary tool for monitoring the distribution and diversity of amphibians. For this purpose, we designed, tested, validated, and optimized 14 species‐specific assays on genomic DNA extracted from tissue samples to use for quantitative polymerase chain reaction (qPCR) setups targeting mitochondrial DNA from amphibians in fresh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 85 publications
0
10
0
Order By: Relevance
“…This may prove especially important due to recent increased focus on ethical insect monitoring and the shifting public opinion of insects [ 80 ]). Importantly, it has been shown that citizen scientists with minimal training are effective in eDNA sampling [ 72 ], thus opening participation to people who have previously been under-served, and participants can even be involved in the corresponding laboratory analyses [ 81 , 82 ]. Furthermore, such participation can enhance citizen scientists' understanding of biodiversity, ecosystems, and the principles of eDNA [ 73 , 83 ].…”
Section: Technology As An Enabler—opening Up New Research Avenuesmentioning
confidence: 99%
“…This may prove especially important due to recent increased focus on ethical insect monitoring and the shifting public opinion of insects [ 80 ]). Importantly, it has been shown that citizen scientists with minimal training are effective in eDNA sampling [ 72 ], thus opening participation to people who have previously been under-served, and participants can even be involved in the corresponding laboratory analyses [ 81 , 82 ]. Furthermore, such participation can enhance citizen scientists' understanding of biodiversity, ecosystems, and the principles of eDNA [ 73 , 83 ].…”
Section: Technology As An Enabler—opening Up New Research Avenuesmentioning
confidence: 99%
“…Several research groups have found great success in inviting school students to participate in citizen science projects with examples of primary and secondary schools collecting insects via Malaise traps (Steinke et al, 2017), testing the ability of schoolchildren to accurately estimate the strength of biotic interactions (Castagneyrol et al, 2020), letting high school students identify archaeological leather fragments with protein analysis (Brandt et al, 2022) or when high school students conduct eDNA analysis in order to detect distribution of amphibians (Knudsen et al, 2023). The schools represent a vast number of participants, students feel engaged in the work and have a positive scientific learning outcome when the teachers are able to combine the citizen science labor with school curriculum.…”
Section: Using Citizen Science and High School Students To Investigat...mentioning
confidence: 99%
“…Engaging and training citizen scientists in advanced laboratory analysis, such as the monitoring of environmental DNA (eDNA) in water samples, has promising applications for large-scale national eDNA surveillance of aquatic species that can be used in governmental mapping and conservation efforts (Tøttrup et al, 2021;Knudsen et al, 2023). In this paper we will showcase the development of an existing citizen science project with focus on eDNA monitoring towards a more comprehensive method for engaging volunteers in field sampling and laboratory analysis.…”
Section: Introduction 1environmental Dna For Species Monitoringmentioning
confidence: 99%
See 2 more Smart Citations